Methodological Insights of Action Research in Doctoral Studies within Education Disciplines: A Systematic Review - Tee, Tze Kiong; Chia, Swee Yee (Rsis, 2025)
Action research (AR) has emerged as a preferred methodology among practice-based doctoral candidates, particularly in education. In conjunction, having a thorough understanding of AR methodology in doctoral studies is a must. Thus, this article investigated the methodology of AR used in doctoral studies within the education disciplines from January 2013 to October 2024. The study included eight ProQuest doctoral dissertations and twelve articles from the Scopus database, selected based on relevance to AR methodology, focus on education disciplines, and methodological rigour. This study focuses on theoretical frameworks, AR models and types, data collection methods, sampling techniques, and sample sizes employed by action researchers. The findings revealed that Grounded Theory was the most commonly utilised theoretical framework, supporting iterative theory development to address complex educational challenges. The flexibility of AR models allows researchers to adapt methodologies to specific contexts, enhancing study efficacy and responsiveness. Traditional AR methods remain widely used due to their seamless integration into professional practices. The duration of AR projects varied, but at least one AR cycle was needed to tailor timelines to issue complexity. Interviews emerged as the primary data collection method, supplemented by questionnaires and focus groups. Most studies employed convenience sampling, with quantitative samples ranging from 25 to 275 participants and qualitative cohorts comprising eight to eleven individuals. This approach aligns with AR’s focus on addressing practical problems and fostering self-improvement, ensuring researchers balance data collection with meaningful insights. Although AR findings are not widely generalisable, their adaptability enables researchers to develop context-specific interventions tailored to the unique needs of educational settings. The iterative nature of AR fosters evidence-based improvements, reflective practice, participatory engagement, and real-time problem-solving. Future research should integrate structured frameworks, adopt mixed-methods approaches, and engage stakeholders to enhance the credibility and applicability of findings, contributing to a deeper understanding and more effective implementation of AR in educational research.